2015
DOI: 10.1103/physrevd.92.036001
|View full text |Cite
|
Sign up to set email alerts
|

Modulated bimaximal neutrino mixing

Abstract: The present article is an endeavor to look into some fruitful frameworks based on "Bi-maximal" neutrino mixing, from a model independent stand. The possibilities involving the correction or attenuation of the original BM mixing matrix, followed by GUT-inspired charged lepton correction are invoked. The "symmetry-basis" thus constructed, accentuates some interesting facets such as: a modified QLC relation, θ12 + θc ≈ π 4 − θ13 cos(nπ − δCP ), a possible link up between neutrino and charged lepton sectors, θ ν 1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 83 publications
2
10
0
Order By: Relevance
“…At finite temperature, uniform binary Bose gases have been worked out using the Bogoliubov approach [35], Hartree-Fock theory [36] and a large-N approximation * a.boudjemaa@univ-chlef.dz [37]. The phase separation, the dynamics, and the thermalization mechanisms of trapped binary mixtures at finite temperatures have been also examined utilizing the local-density approximation [38], HFB-Popov theory [39], and the Zaremba-Nikuni-Griffin (ZNG) model [40][41][42]. Very recently, effects of quantum and thermal fluctuations in a two-component Bose gas with Raman induced spin-orbit coupling have been analyzed using the HFB-Popov theory [43].…”
Section: Introductionmentioning
confidence: 99%
“…At finite temperature, uniform binary Bose gases have been worked out using the Bogoliubov approach [35], Hartree-Fock theory [36] and a large-N approximation * a.boudjemaa@univ-chlef.dz [37]. The phase separation, the dynamics, and the thermalization mechanisms of trapped binary mixtures at finite temperatures have been also examined utilizing the local-density approximation [38], HFB-Popov theory [39], and the Zaremba-Nikuni-Griffin (ZNG) model [40][41][42]. Very recently, effects of quantum and thermal fluctuations in a two-component Bose gas with Raman induced spin-orbit coupling have been analyzed using the HFB-Popov theory [43].…”
Section: Introductionmentioning
confidence: 99%
“…For quantum mixtures, this question was addressed long time ago in the context of 3 He-4 He liquids [2], and more recently for mixtures of quantum gases [3,4]. In particular, weakly interacting binary Bose gases occupying two different hyperfine states are the simplest, yet interesting example of quantum mixtures, for which the problem of miscibility has been intensively investigated, both experimentally [5][6][7][8][9] and theoretically [10][11][12][13][14][15][16][17][18][19][20][21]. The theoretical studies have revealed that, in the zero temperature mean field regime, the mixture is stable against phase separation if the inequality g 2 12 < g 11 g 22 holds, where g ij is the coupling constant for the intra-species (g 11 and g 22 ) and inter-species (g 12 ) interactions [3,[10][11][12][13][14].…”
mentioning
confidence: 99%
“…The theoretical studies have revealed that, in the zero temperature mean field regime, the mixture is stable against phase separation if the inequality g 2 12 < g 11 g 22 holds, where g ij is the coupling constant for the intra-species (g 11 and g 22 ) and inter-species (g 12 ) interactions [3,[10][11][12][13][14]. At finite temperature, theoretical studies have mainly focused on harmonically trapped systems, by means of the Hartree-Fock [15][16][17], Zaremba-Nikuni-Griffin [18] and Hartree-Fock-Bogoliubov [19][20][21] theories. Although they differ in the treatment of the intra-species interaction, all the above approaches treat the inter-species coupling at the mean-field level, thereby providing an inaccurate description of the thermal fluctuations associated with the spin degree of freedom.…”
mentioning
confidence: 99%
“…Of particular importance for the current investigation are coefficients c( n, m) appearing in expansion (14) and defined as c( n, m) = n, m|ψ 0 (17) which will be used to introduce the quantum counterparts of indicators (8) and (9). The diagonalization of Hamiltonian (1) is carried out for extended sets of model parameters, in such a way to explore vast regions of the (α, β)-plane (recall formulas (6)), also in relation with the presence of non-negligible hoppings T a and T b .…”
Section: Quantum Critical Indicatorsmentioning
confidence: 99%
“…Such systems, realized by means of both homonuclear [1] and heteronuclear [2] components, show how the interplay among the intra-species and the inter-species repulsion, the tunneling effect and the fragmentation induced by the periodic potential strongly affects the mixing properties and gives rise to an extremely rich phenomenology. This includes spatial phase separation in large-size lattices [3,4], mixing properties of dipolar bosons [5], quantum emulsions [6,7], the structure of quasiparticle spectrum across the demixing transition [8], and the influence on phase separation of thermal effects [9], interspecies entanglement [10], and asymmetric boson species [11]. Further aspects concerning the interlink between demixing and the dynamics of mixtures have been explored in [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%